Factors Affecting Tax Avoidance (Study in Manufacturing Companies of Building Construction Sub-Sector of Indonesia Stock Exchange) - Marchell Teja; Herry Goenawan Soedarsa; Khairudin Khairudin (Lafadz Jaya Publisher, 2024)
According to The State of Tax Justice 2020 report, Indonesia's position in tax avoidance cases is ranked fourth in Asia. This research aims to examine the factors that affect tax avoidance in manufacturing companies on the Indonesia stock exchange. This research covers the building construction manufacturing business of the Indonesia Stock Exchange in 2021–2022. Purposive sampling was used in this study and produced 34 samples. This research uses descriptive statistics, classical assumption tests, and multiple linear regression. This research found that Audit Quality and Profitability have a significant positive impact on Tax Avoidance.